From actinic keratosis to cutaneous squamous cell carcinoma: the key pathogenesis and treatments - Li, Zhenlin; Lu, Fangqi; Zhou, Fujin; Song, Dekun; Chang, Lunhui; Liu, Weiying; Yan, Guorong; Zhang, Guolong (Frontiers in Immunology, 2025)
Cutaneous squamous cell carcinoma (cSCC) is the second most common non-melanoma skin cancer, among which 82% arise from actinic keratosis (AK) characterized by lesions of epidermal keratinocyte dysplasia. It is of great significance to uncover the progression mechanisms from AK to cSCC, which will facilitate the early therapeutic intervention of AK before malignant transformation. Thus, more and more studies are trying to ascertain the potential transformation mechanisms through multi-omics, including genetics, transcriptomics, and epigenetics. In this review, we gave an overview of the specific biomarkers and signaling pathways that may be involved in the pathogenesis from AK to cSCC, pointing out future possible molecular therapies for the early intervention of AK and cSCC. We also discussed current interventions on AK and cSCC, together with future perspectives.